Systematic Review: Heat Treatments on Phenolic Content, Antioxidant Activity, and Sensory Quality of Malaysian Mushroom: Oyster (Pleurotus spp.) and Black Jelly (Auricularia spp.) - Izham, Inshirah; Avin, Farhat; Raseetha, Siva (Frontiers in Sustainable Food Systems, 2022)
Pleurotus spp. and Auricularia spp. are popular species consumed by the Malaysian community. Recently, due to increased awareness, both mushrooms are also being consumed for their bioactive compounds, ergothioneine, and antioxidant properties and has been used since earlier ages as therapeutic remedies. The bioactive compounds such as phenol, flavonoid and ergothioneine found in both Pleurotus and Auricularia mushrooms were explored. Differences in heat treatments (microwave, hot air drying, and solar drying) and cooking methods may affect the content of bioactive compounds and their properties. Similarly, sensory acceptance by consumers may be affected too. Antioxidant properties using DPPH (1,1-diphenyl-2-picryl-hydrazyl) radical and FRAP (ferric reducing antioxidant power) assay of both raw and heat-treated mushrooms are included. Microwave drying retained color characteristics and bioactive compounds in both mushrooms. To add value to this review, a survey on the consumption pattern of Pleurotus and Auricularia species among Malaysians has been conducted online and concluded that Pleurotus species is the most considered species compared to Auricularia mushroom and almost half of the respondents were not aware that heat may deplete nutritional contents in mushroom despite agreeing both gave beneficial health in diets.